Propensity score matching analysis to evaluate the comparative effectiveness of daratumumab versus real-world standard of care therapies for patients with heavily pretreated and refractory multiple myeloma - Kumar, Shaji; Goldschmidt, Hartmut (Leukemia and lymphoma, 2019)
Daratumumab is a CD38-directed monoclonal antibody approved for treating multiple myeloma (MM). Propensity score matching (PSM) based on individual patient data (IPD) was conducted to compare overall survival (OS) and progression-free survival (PFS) for daratumumab versus real-world standard of care (SOC). IPD for patients with relapsed and refractory (RR) MM treated with daratumumab monotherapy were from the GEN501 and SIRIUS studies; IPD for patients treated with SOC were from an International Myeloma Working Group (IMWG) chart review of patients with RRMM. Prior to PSM, patients treated with daratumumab had significantly longer OS (median 20.1 vs. 10.1 months, hazard ratio [HR] = 0.51 [0.39-0.67]) and PFS (median 4.0 vs. 2.8 months, HR = 0.73 [0.58-0.92]) than patients treated with SOC therapies. After PSM, daratumumab maintained a significantly prolonged OS (19.9 vs. 9.2 months, HR = 0.44 [0.31-0.63]) and PFS (3.9 vs. 1.6 months, HR = 0.56 [0.42-0.74]) compared with SOC.
Published online: 09 May 2018
Gesehen am 24.10.2019